Strategic R&D cooperatives - Jeroen Hinloopen (Fondazione Eni Enrico Mattei (FEEM), 1998)
Allowing firms to cooperate in their R&D is an industrial policy, which has received much attention in recent economics literature. Many of these contributions are based on the seminal analysis of d'Aspremont and Jacquemin (1988). We provide a general version of their model, which encompasses several recent contributions in the literature. With this general model we then examine the main arguments against and in favour of sustaining R&D cooperatives.
Keywords: D43; L13; L41; 330; Differentiated oligopoly; Cournot competition; Bertrand competition; Spillovers; Forschungskooperation; Oligopol; Unvollkommener Wettbewerb; Spillover-Effekt; Spieltheorie; Theorie